Spiritual/religious coping strategies and religiosity of patients living with cancer in palliative care - Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; deSousa Matos, Ticiane Dionízio [UNESP]; Vitória, Amanda [UNESP]; Segalla, Zorzi [UNESP]; Jaqueline, Fary [UNESP]; Generoso, Fortaleza [UNESP]; de Oliveira, Cesar (Mark Allen Group, 2023)
Background: The palliative care provided to cancer patients should also contemplate the psychological and spiritual dimensions of care. Aims: This study aimed to compare religiosity and spiritual/religious coping (SRC) of cancer patients in palliative care with a group of healthy volunteers and determine whether sociodemographic characteristics affected this association. Methods: This was a case-control study conducted with 86 patients living with cancer from an outpatient palliative care clinic of the São Paulo State University (UNESP) medical school, Botucatu, Brazil and 86 healthy volunteers.The brief Spiritual/Religious Coping Scale (SRCOPE) and the Duke University Religion (DUREL) Index were used as a brief measure of ‘religiosity’. Results: All 172 participants reported to be religious and, overall, made very little use of SRC strategies. DUREL scores were negatively associated with religious practice (P<0.01) and positive SRC (P<0.01). Age was associated with non-organisational religious activities and intrinsic religiosity (P<0.01); and income was associated with intrinsic religiosity (P<0.04). Positive SRC was negatively associated with the palliative group (P=0.03) and DUREL index (P<0.01). Negative SRC was positively associated with the palliative group (P=0.04) and negatively associated with education level (P=0.03) and practice of religion (P<0.01). Conclusion: All participants reported to be religious; however, their use of SRC strategies was very low. Positive religious coping was the most prevalent score. Negative religious coping was more common in the palliative care group compared to healthy volunteers. There is an association between religious coping and religiosity in palliative cancer care patients.
Keywords: cancer; nursing; palliative care; religiosity; spirituality